2017
DOI: 10.1002/qj.3158
|View full text |Cite
|
Sign up to set email alerts
|

Does the lower stratosphere provide predictability for month‐ahead wind electricity generation in Europe?

Abstract: Wind power is playing an increasingly important role in Europe's electricity generation. Accurate forecasts of wind‐power output on various spatial and temporal scales are therefore of high interest for the energy industry. However, predictability of near‐surface wind on subseasonal time‐scales has received relatively little attention. The stratosphere is an important source of subseasonal predictability in winter. Here, we study the implications of the lower stratospheric circulation for month‐ahead wind elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 41 publications
2
41
0
Order By: Relevance
“…Indeed, the change in JFM mean SLP in the SSW experiment in the North Atlantic sector can be almost entirely explained by the projection onto the NAO pattern (not shown). This is consistent with previous studies that show the SLP response to SSWs in the North Atlantic sector resembles a negative NAO (e.g., Charlton and Polvani 2007;HS14) and that stratospheric variability does not strongly affect North Atlantic weather regimes that are independent of the NAO (Beerli and Grams 2019).…”
Section: E Relationship To the Leading Patternssupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, the change in JFM mean SLP in the SSW experiment in the North Atlantic sector can be almost entirely explained by the projection onto the NAO pattern (not shown). This is consistent with previous studies that show the SLP response to SSWs in the North Atlantic sector resembles a negative NAO (e.g., Charlton and Polvani 2007;HS14) and that stratospheric variability does not strongly affect North Atlantic weather regimes that are independent of the NAO (Beerli and Grams 2019).…”
Section: E Relationship To the Leading Patternssupporting
confidence: 93%
“…This study makes a first attempt to connect the time mean surface response to SSWs with the regime behavior of the North Atlantic eddy-driven jet and provides a complementary approach to other work that focuses on storm-track and jet variability. For example, previous studies have related jet regimes to the leading modes of variability, such as the NAO (e.g., Woollings et al 2008Woollings et al , 2011, and two studies have related the surface response to stratospheric anomalies to daily weather regimes (Charlton-Perez et al 2018;Beerli et al 2017). We have attempted to bridge the traditional view of a time-averaged NAO2 response and southward shift of the jet following SSWs with the characteristics of daily EDJ variability.…”
Section: Discussionmentioning
confidence: 99%
“…Regimes describe the large‐scale atmospheric configuration on any given day and are based on recurrent and persistent patterns in the large‐scale circulation (Michelangeli et al, ). Because regimes exist on longer timescales than synoptic weather patterns, they provide an opportunity for longer‐range prediction, useful for the energy sector (Beerli et al, ; Grams et al, ) and for the prediction of cold weather extremes in winter (Ferranti et al, ). Charlton‐Perez et al () described the influence of the strength of the SPV on weather regimes in the North Atlantic, where the tropospheric response to changes in the stratospheric circulation is typically largest.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive body of research has suggested that extreme states of the stratospheric polar vortex provide extended-range predictability. Extreme states of the stratospheric polar vortex modulate the probabilities for large-scale weather patterns on subseasonal time scales (e.g., Baldwin and Dunkerton, 2001;Tripathi et al, 2015a;Beerli et al, 2017). For example, there is an enhanced probability of a positive (negative) North Atlantic Oscillation (NAO) following strong (weak) stratospheric polar vortex conditions (Baldwin and Dunkerton, 2001).…”
Section: Introductionmentioning
confidence: 99%